2021
DOI: 10.1097/htr.0000000000000642
|View full text |Cite
|
Sign up to set email alerts
|

Association of Self-Paced Physical and Cognitive Activities Across the First Week Postconcussion With Symptom Resolution in Youth

Abstract: Objective: To examine the association of objectively measured, self-paced physical and cognitive activities across the first week postconcussion with symptom resolution in youth. Setting: Emergency department or concussion clinics. Participants: Youth aged 11 to 17 years with physician-confirmed concussion. Design: Prospective cohort with repeated measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…More specifically, one study showed that the number of accelerometer-measured steps from days 1-3, 4-5, and 6-7 post-injury were significantly correlated with symptom scores at each of these intervals, and the increased activity (i.e., number of steps) from days 1-3 post-injury predicted lower activity on days 4-5 post-injury 33 . A second study by this group reported that there was no association between physical and cognitive activity and time to concussion recovery 34 . Another group studied male youth hockey players wearing accelerometers in the early stages of injury and found that those in the “high” activity group (based on a median split, performing more than 148.5 minutes of MVPA/day) took significantly longer to recover than those in the “low” activity group 32 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…More specifically, one study showed that the number of accelerometer-measured steps from days 1-3, 4-5, and 6-7 post-injury were significantly correlated with symptom scores at each of these intervals, and the increased activity (i.e., number of steps) from days 1-3 post-injury predicted lower activity on days 4-5 post-injury 33 . A second study by this group reported that there was no association between physical and cognitive activity and time to concussion recovery 34 . Another group studied male youth hockey players wearing accelerometers in the early stages of injury and found that those in the “high” activity group (based on a median split, performing more than 148.5 minutes of MVPA/day) took significantly longer to recover than those in the “low” activity group 32 .…”
Section: Discussionmentioning
confidence: 94%
“…Accelerometers have been used in many pediatric neurological and chronic disease populations to compare the activity of these children to their typically developing peers 29-31 , providing insights about the intensity, time, and frequency of physical activity that recall surveys cannot capture. In concussion, accelerometry has been used to begin to understand the relationship between concussion symptoms and activity 32-34 , although no controlled studies have quantified levels of sedentary time and habitual physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings collectively highlight the need for flexible management and return-to-activity progressions for adolescents with concussion, ideally incorporating self-management by the patient and family. A recent study found that self-paced physical and cognitive activities in the acute recovery phases do not seem to accelerate or delay recovery 30. The American Congress of Rehabilitation Medicine Mild TBI Task Force has developed some expert-guided recommendations that clinicians may find helpful in communicating strategies for self-pacing to adolescents and their families 31.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we try to get them back fairly quickly." This is backed up by a recent study by Yang et al who found that self-paced physical and cognitive activity when recovering from concussion was neither helpful nor damaging to the child [56].…”
Section: Managementmentioning
confidence: 98%